MODIFIKASI MESIN BUBUT SEBAGAI MESIN PENGUJI INLINE TYPE INJECTION PUMP - Aep Surahto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2008)
A Diesel Motor is need regular maintenance and repairs. Regular maintenance of diesel engine fuel system needs an engine testbed The price of pump infection testing machine is a major constraint in university labs majoring in mechanical engineering. Test Bench or Injection Pump test machine can be designed by modifying a lathe with a speed of at least 2,000 rpm. The result of this design was very helpful Test Bench with lower prices without lowering the quality requirements of a testing machine Injection Pump, which can help a Mechanical Engineering 's Labs.